EFEKTIFITAS AROMATHERAPY LEMON TERHADAP PENGURANGAN NYERI PERSALINAN, LAMA PERSALINAN KALA II DAN FETAL OUTCOME DI KLINIK HENI KASIH - Laurena Ginting; Masta Melati Hutahaean; Lenny Lusia Simatupang (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
Abstract Pain is an unpleasant and complex condition. The fear of labor pain causes a reduction in blood flow and oxygen to the uterus giving rise to uterine inertia (inadequate contraception). Lemon aromatherapy has anesthetic, analgesic and sedative effect. The purpose of this study was to examine the effectiveness of lemon aromatherapy on pain reduction, length of labor and fetal outcome. The design of this study used a quasi experimental design with a one group approach, measurements were taken in one group given treatment by giving lemon aromatherapy and comparing the second group as a control not given aromatherapy lemon. The population of all women giving birth at the Heny Kasih clinic. The sample in this study was taken by purposive sampling. The research sample consisted of 30 women giving birth, 15 giving birth treatment and 15 giving birth as a control group. Sampling was carried out with inclusion criteria, namely in the first phase of active phase, physiological labor, willing to be the subject of research, single pregnancy, presentation of the back of the head, and not yet receiving pharmacological therapy. Data analysis was done by looking at the differences in the 2 variables because the data were not normally distributed then the statistical tests used were Mann Whitney. The results of research on the effectiveness of lemon aromatherapy on labor pain p = 0.019 where the value of p <0.005, the second time showed no effectiveness of lemon aromatherapy on the second time p = 0.451 greater than p = 0.005 in the fetal outcome showed no effectiveness of lemon aromatherapy against fetal outcome p = 1,000 is greater than p = 0.005. Keywords: Aromatherapy, Lemon, Labor_Pain, Time_of _kala II, Fetal_Outcome